Studencki ruch naukowy w systemie nauki akademickiej = Student scientific movement in academic study system - Smużewska, Marcelina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Student scientific movement in Poland is over 150 years old. Its history is best recognized by a model (which is an idealization tool) as the theory of social movements poses too many problems. In this way three models emerge: traditional (1851-1947), socialist (1948-1989) and contemporary. In all three models a scientific circle is a dominant organization form, having the features of community and association. Institutional processes influence the activity of student movement in a negative way.
Keywords: studencki ruch naukowy; organizacje studenckie; szkolnictwo wyższe; studenci